Analysis of interfacial adhesion properties of nano-silica modified asphalt mixtures using molecular dynamics simulation. (20th September 2020) - Long, Zhengwu; You, Lingyun; Tang, Xianqiong; Ma, Wenbo; Ding, Yanhuai; Xu, Fu
Highlights: Aggregate surface irregularity influences its adhesion strength with asphalt. Seawater erosion affects the interfacial adhesion properties of asphalt mixtures. Nano-silica modification reduces the sensitivity to oxidation aging and seawater erosion. Abstract: The presence of nano-silica can reduce the sensitivity to moisture damage of asphalt mixtures and improve the anti-oxidation aging ability of asphalt binder. In the present work, the interface adhesion of nano-silica modified asphalt to aggregate surfaces at the different interfacial situations (aggregate surface irregularity and seawater erosion) were investigated using molecular dynamics (MD) simulations. The sodium chloride solution is used to simulate seawater erosion. The asphalt 12-component molecular model is used for the analysis of thermodynamic properties such as density, the ratio of free volume, and cohesive energy density. Molecular structure properties of asphalt on the aggregate surfaces were analyzed by radial distribution function (RDF), relative concentration (RC), and mean square displacement (MSD) of asphalt molecule. The interface adhesion properties were investigated by calculating the work of adhesion at the different interfacial situations. The results show that oxidation aging promotes the asphaltene aggregate on the surface of the silica aggregate, while the effect of nano-silica is reversed. Increasing the surface roughness of the aggregate enhanced its adhesion strength. The asphalt mixtures are less resistant to sodium chloride solution erosion than water damage. Compared with the original asphalt binder, oxidized asphalt is more susceptible to damage by water or sodium chloride solution. The presence of nano-silica reduces the susceptibility of asphalt mixture to water damage or sodium chloride solution erosion. The research findings provide insights to more fully understand the micromechanisms of interface adhesion failure between asphalt binder and aggregate.